2018
DOI: 10.5539/ies.v11n7p125
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning, Conditional Knowledge and Professional Development at University of Nairobi, Kenya—Focusing on Preparedness for Teaching Practice

Abstract: Experiential learning requires teacher educators to equip trainee teachers with opportunities for effective preparedness in teaching and professional subjects, co-curricular activities and in micro-teaching vital for professional development. The experiential learning opportunities, conditional knowledge, preparedness and performance during teaching practice provide basis for predicting professional competence and success for effective teaching. Conditional knowledge entails application of critical thinking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Some of the students themselves started the task as they used previous knowledge regarding it. It was also revealed through the data that creative thinking and problem solving and creative thinking skills are the tire need of modern times which can be transmitted through experiential learning as evidenced by the study Amolloh, Lilian, and Wanjiru (2018), whose findings showed that problem solving and critical thinking abilities and knowledge could be availed through experiential learning. Another study's findings revealed that the E.L. model could foster creative thinking skills in students (Meyer, 1982;Sheih & Chang, 2014).…”
Section: Discussion and Findingsmentioning
confidence: 88%
“…Some of the students themselves started the task as they used previous knowledge regarding it. It was also revealed through the data that creative thinking and problem solving and creative thinking skills are the tire need of modern times which can be transmitted through experiential learning as evidenced by the study Amolloh, Lilian, and Wanjiru (2018), whose findings showed that problem solving and critical thinking abilities and knowledge could be availed through experiential learning. Another study's findings revealed that the E.L. model could foster creative thinking skills in students (Meyer, 1982;Sheih & Chang, 2014).…”
Section: Discussion and Findingsmentioning
confidence: 88%
“…The principles and practices of experiential learning have been widely adopted in models, programs to conduct academic courses such as competency-based education (Miettinen, 2000;Ahmed, 2018), professional training (Richard, Cowen & Kolb, 1995;Akhigbe, 2018;Amolloh, Lilian & Wanjiru, 2018;Tiessen, Grantham & Cameron, 2018;Stefano, Ruvolo & Mauro, 2019), college programs for adult learners, and prior learning assessment (Simosko, 1998;Andrews, Brown & Mesher, 2018;Awidi & Paynter, 2019;Bhati & Song, 2019), service learning (Angela, Bruce, Kevin, Mandar & Kurtis, 2011;Aissaoui, Alami, Oughdir & Allioui, 2018), problem-based learning (Bethell & Morgan, 2011;Gomez & Nasir, 2019;Harfitt, 2019;Stephanie, Lockwood, Hill & Randell, 2020;Setiyani, Harnanik, Lianighsih & Susilowati, 2020), action learning (Louise, 1994). The experiential lessons provide students with an opportunity to experience concepts, give students a more productive, more meaningful understanding of course concepts, and of how they operate in the real world.…”
Section: The Process Of Instruct Students To Perform Experiential Learning Activities In the Schoolsmentioning
confidence: 99%
“…When one uses their conditional knowledge, they regulate and direct their conceptual and procedural knowledge. Amolloh, Lilian, and Wanjiru (2018) asserted that conditional knowledge aids critical thinking and problem solving at a higher level.…”
Section: Types Of Knowledgementioning
confidence: 99%
“…Bransford et al (2000) noted that one thing that sets experts apart is that their knowledge is conditionalized (see also Renkl & Mandl, 1996;Swan et al, 2020;Whitehead, 1929). Not only do they have knowledge of concepts and procedures, but they also understand the conditions under which to apply that knowledge (Amolloh et al, 2018;Elvira et al, 2017;Lorch, Lorch, & Klusewitz, 1993). As Barrotta and Montuschi (2018) put it, experts have "knowledge of the specific relevant circumstances to which [theory] is applied" (p. 390).…”
Section: Types Of Knowledgementioning
confidence: 99%